1996
DOI: 10.1038/bjc.1996.156
|View full text |Cite
|
Sign up to set email alerts
|

Human liver cancer cells and endothelial cells incorporate iodised oil

Abstract: Summary lodised oil (lipiodol) al., 1985). Lipiodol, an iodinated derivative of poppyseed oil, has been in use for over a decade as a vehicle for targeted cytotoxic or radiotherapeutic treatment of unresectable HCCs. When injected into the hepatic artery the oil is retained by HCCs for several weeks to over a year, but is cleared from normal liver parenchyma within 7 days (Nakakuma et al., 1979). Trials using lipiodol in conjunction with cytotoxic drugs such as doxorubicin, epidoxorubicin, aclarubicin, 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…Using previously described method, Lipiodol uptake by all the cancer cell lines and by the endothelial cells was demonstrated on light and electron microscopy as early as 3 h (Al-Mufti et al, 1996). In this study, 131 I-Lipiodol was also demonstrated within the cancers cells and the benign endothelial cells as early as 6 h. Lipiodol alone as a control (without 131 I) had no effect on the cell growth or viability when compared to the controls, and was therefore not cytotoxic to any of the cell lines used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously described method, Lipiodol uptake by all the cancer cell lines and by the endothelial cells was demonstrated on light and electron microscopy as early as 3 h (Al-Mufti et al, 1996). In this study, 131 I-Lipiodol was also demonstrated within the cancers cells and the benign endothelial cells as early as 6 h. Lipiodol alone as a control (without 131 I) had no effect on the cell growth or viability when compared to the controls, and was therefore not cytotoxic to any of the cell lines used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism of Lipiodol uptake is poorly understood, this study confirms our previous reports that Lipiodol is taken up and is retained in the form of cytoplasmic membrane-bound vesicles (Al-Mufti et al, 1995). Quantification methods using computer-assisted image analysis of the uptake of Lipiodol by the malignant and the non-malignant cell lines (Al-Mufti et al, 1996) have revealed that cancer cell lines, unlike non-malignant cells, are unable to expel Lipiodol. This may further enhance the cytotoxic effect of 131 I-Lipiodol in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for bilobar disease 2 separate treatment sessions are needed, whereas with 131 I-lipiodol a single infusion into the common hepatic artery beyond the gastroduodenal artery will result in tumor uptake in both lobes. In addition, the mechanism of action of 131 I-lipiodol, which involves direct uptake into tumor cells, results in a higher tumor radiation dose than do the methods requiring embolization of radioactive particles (9). In a prospective phase 2 study of 65 patients with biopsy-proven HCC, the administration of TheraSpheres However, there are 2 major caveats to the use of these techniques, as they are essentially embolic in nature: severe liver dysfunction and PVT represent theoretic contraindications, as in TACE.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of HCC was made according to the criteria of the 2000 Barcelona European Association for Study of the Liver consensus conference (9). At baseline (the day of the first session of intraarterial treatment), standard laboratory data and imaging characteristics of the HCC and liver from cross-sectional imaging (CT or MRI) were recorded.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The fate of LIP in the hepatic vascular system LIP (also known as Ethiodol ® ) is an iodinated and ethylated poppy seed oil that consists of ethyl linoleate (70% w/w), ethyl oleate (15% w/w), ethyl palmitate (10% w/w), ethyl stearate (5% w/w), and contains 37-39% iodine (400 mg/ml) [44,45]. Following injection into the HA, LIP is accumulated in tumor tissue for at least 3 months, as lipid layers (nonglobular) extracellularly and as droplets (globular) intracellularly (Figure 3) [7,46].…”
Section: Lipmentioning
confidence: 99%